2016
DOI: 10.1080/17451000.2016.1183792
|View full text |Cite
|
Sign up to set email alerts
|

Growth and maturity of the spider crab Halicarcinus planatus (Brachyura: Hymenosomatidae) females in the southwestern Atlantic Ocean. Can these parameters be influenced by the population sex ratio?

Abstract: The Halicarcinus planatus populations of the southwestern Atlantic Ocean show a highly variable sex ratio and a large size overlapping between females in the last immature instar (ADO) and mature (MAT) females. We hypothesized that these facts are related and that female impregnation has a central role in this relation. Non-impregnated ADO females delay maturity and would continue to grow, leading to size overlapping. This scenario is most probable in populations with a scarcity of males and could affect the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In February 2010, a living and mature female of the brachyuran crab Halicarcinus planatus (Fabricius, 1775) was reported in shallow, subtidal waters of Deception Island (Western Antarctic Peninsula) (Aronson et al, 2015) (Figure 3). Halicarcinus planatus is usually distributed in shallow water areas of southern South America and along coastal areas of some sub‐Antarctic Islands (Falkland, Marion, Crozet, Kerguelen and Macquary islands) (Aronson et al, 2015; Boschi et al, 1969; Richer de Forges, 1977; Varisco et al, 2016). This little crab (shell diameter from 15 to 20 mm, Figure 3) is an opportunistic feeder (Boschi et al, 1969) that is commonly found sheltered below intertidal and subtidal rocks (Richer de Forges, 1977; Vinuesa & Ferrari, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In February 2010, a living and mature female of the brachyuran crab Halicarcinus planatus (Fabricius, 1775) was reported in shallow, subtidal waters of Deception Island (Western Antarctic Peninsula) (Aronson et al, 2015) (Figure 3). Halicarcinus planatus is usually distributed in shallow water areas of southern South America and along coastal areas of some sub‐Antarctic Islands (Falkland, Marion, Crozet, Kerguelen and Macquary islands) (Aronson et al, 2015; Boschi et al, 1969; Richer de Forges, 1977; Varisco et al, 2016). This little crab (shell diameter from 15 to 20 mm, Figure 3) is an opportunistic feeder (Boschi et al, 1969) that is commonly found sheltered below intertidal and subtidal rocks (Richer de Forges, 1977; Vinuesa & Ferrari, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Previous to this record, Stebbing (1914) reported this species in Macdougal Bay, South Orkney Islands; however, the reliability of this occurrence has been questioned, considering its circum‐Subantarctic distribution (Aronson et al, 2015; Diez & Lovrich, 2010; Thatje & Arntz, 2004; Yaldwyn, 1965). Halicarcinus planatus is the only hymenosomatid crab that inhabits shallow waters (Garth, 1958; Varisco et al, 2016) of southern South America and the Subantarctic Falkland/Malvinas, Marion, Crozet, Kerguelen and Macquarie islands (Aronson et al, 2015; Boschi et al, 1969; Griffiths et al, 2013; Melrose, 1975; Richer De Forges, 1977). This small crab (carapace width up to 15 and 20 mm for female and male, respectively, in Punta Arenas; Figure 1) is an opportunistic feeder (Boschi et al, 1969) commonly found sheltered under rocks in the intertidal and subtidal zones, in between holdfasts of the giant kelp Macrocystis pyrifera or sheltered in hydrozoans and mussel colonies (Chuang & Ng, 1994; Richer De Forges, 1977; Vinuesa & Ferrari, 2008).…”
Section: Introductionmentioning
confidence: 99%